EFFECT OF VIDEO-BASED HEALTH EDUCATION ON HPV VACCINATION KNOWLEDGE AND INTEREST - Fauziyah, Anny; Purwaningsih, Tinah; Yudyarto, Hudinoto Eko (Siklus : Journal Research Midwifery Politeknik Tegal, 2024)
Cervical cancer is the highest type of cancer in Indonesia after breast cancer. In 2022 there will be 660 thousand new cases, and at least 350,000 women worldwide will die from cervical cancer. Prevention efforts that can be taken are HPV vaccination. The 2022-2024 Immunization Introduction Program only targets elementary school girls in grades V and VI, while outside the target group it is carried out independently. Women's low knowledge about HPV affects their confidence in vaccination. The research aims to measure the effectiveness of providing Health Education with videos on the level of knowledge and interest in HPV Vaccination of Tegal City High School Female Students. This research used a quasi-experimental design, the research population was 621 female students at SMUN 3 Tegal City, the research sample was 30 respondents in the intervention group and 30 respondents in the control group. Data collection using questionnaires, data analysis using Mc. Nemar's test and Fisher's test. The research results concluded that Health Education with videos had an effective effect in increasing knowledge compared to education without videos (p value 0.00) but was not effective in increasing interest (p value 0.067).